2013
DOI: 10.1002/stem.1298
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β1 Signal is Crucial for Dedifferentiation of Cancer Cells to Cancer Stem Cells in Osteosarcoma

Abstract: Human osteosarcoma harbors a small subpopulation of cancer stem cells (CSCs) that is believed to be associated with tumor metastasis, radioresistance/chemoresistance, local invasion, and poor clinical outcome. In this study, we found that transforming growth factor b1 (TGF-b1) signaling and a hypoxic environment dramatically induced selfrenewal capacity in non-stem osteosarcoma cells, which in turn promoted chemoresistance, tumorigenicity, neovasculogenesis, and metastatic potential. Furthermore, blocking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 50 publications
3
112
0
Order By: Relevance
“…The potential plasticity of the CSC phenotype in osteosarcoma was shown by Zhang et al (39). The authors presented that MNNG/HOS, Saos2 and MG63 cells readily formed spheres and that treatment with TGFβ1 or application of hypoxic conditions (both abundant in the bone microenvironment) significantly increased sphere formation suggesting an induction of CSCs through environmental factors.…”
Section: Sphere Formation Assaysmentioning
confidence: 88%
“…The potential plasticity of the CSC phenotype in osteosarcoma was shown by Zhang et al (39). The authors presented that MNNG/HOS, Saos2 and MG63 cells readily formed spheres and that treatment with TGFβ1 or application of hypoxic conditions (both abundant in the bone microenvironment) significantly increased sphere formation suggesting an induction of CSCs through environmental factors.…”
Section: Sphere Formation Assaysmentioning
confidence: 88%
“…Notably, unlike the typical CD31⁻/CD34⁻/PAS⁺ VM, our group found that osteosarcoma stem cells (OSCs) had the capability to construct a CD31-positive vascular network de novo either under hypoxia or upon VEGFA induction [5]. This neo-VM subtype was formed by a type of vascular endothelial cell-like cells that transdiferentiated from OSCs as shown in Figure 3. …”
Section: Vasculogenic Mimicrymentioning
confidence: 99%
“…These cells could also form lipid droplets in an adipogenic diferentiation medium. Gene set enrichment analysis (GSEA) revealed that gene alterations during the process of dediferentiation are closely correlated with chemoresistance and metastasis in OS patients [5].…”
Section: Osteosarcoma Stem Cells and Dediferentiationmentioning
confidence: 99%
See 2 more Smart Citations